Composing a Test for the Fourth Form Pupils. Features of the Test Diagnostic Quality - Kiseliovas, Arkadijus; Kiseliova, Danutė (Acta Paedagogica Vilnensia, 2003)
The investigation is a first attempt to define the concept of the primary school achievements in mathematics, to formulate a methodological frame, to compose and ground the technology of the task selection, to foresee the regulations and conditions of the test administration and to choose statistical methods for the test results analysis. The following diagnostic quality statistical features of the tasks composing the test for the achievements in mathematics meant for the fourth form pupils have been presented: the index of complexity, the standard deviations, the discrimination index, the correlation coefficient with the test, and the estimation rit of the relationship with hypothetic achievements in mathematics. The most interrelated test task groups have been distinguished by Alfa factor analysis method. In addition the inner structure of these groups has been analysed by Alfa factor analysis method. The tables present the coefficients of the tasks with the factor, the parameters of the mathematical factor analysis model: Kaiser-Meyer-Olkin (KMO) coefficient, estimating the usability of the inter-correlation matrix in factor (a1) analysis and the estimation of the factor descriptive power, expressed by the dispersion per cent received by the factor. The information obtained may serve as basis in selecting tasks for another test.
Keywords: primary school; mathematics; teaching; achievements; diagnostic; test